2015
DOI: 10.1177/0022042615580991
|View full text |Cite
|
Sign up to set email alerts
|

Baby Boomers and Cannabis Delivery Systems

Abstract: Findings for this article are derived from our National Institute on Drug Abuse (NIDA)-funded study of older and younger Baby Boomers and marijuana use. We explore Baby Boomers' use of a variety of cannabis products and the motives behind the choices they make concerning these preparations. Cannabis concentrates and edible goods have become increasingly popular over the years. With so many new ways to consume marijuana and a growing number of medical marijuana dispensaries, more and more people are using alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…In a nationally representative study of adults in the US, 29.8 percent of respondents who had ever used cannabis reported consuming it in edible or beverage form (Schauer, King, Bunnell, Promoff, & McAfee, 2016). Additional research finds that edibles are especially popular with medicinal cannabis users (Pacula, Jacobson, & Maksabedian, 2015) as well as with the Baby Boomer generation (Murphy et al, 2015). Surveys conducted in several US states (California, Washington, and Colorado) and Canada found that 11 percent to 26 percent of medicinal cannabis users had consumed an edible cannabis product during their lifetimes (Grella, Rodriguez, & Kim, 2014; Walsh et al, 2013).…”
Section: Overview Of Ediblesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a nationally representative study of adults in the US, 29.8 percent of respondents who had ever used cannabis reported consuming it in edible or beverage form (Schauer, King, Bunnell, Promoff, & McAfee, 2016). Additional research finds that edibles are especially popular with medicinal cannabis users (Pacula, Jacobson, & Maksabedian, 2015) as well as with the Baby Boomer generation (Murphy et al, 2015). Surveys conducted in several US states (California, Washington, and Colorado) and Canada found that 11 percent to 26 percent of medicinal cannabis users had consumed an edible cannabis product during their lifetimes (Grella, Rodriguez, & Kim, 2014; Walsh et al, 2013).…”
Section: Overview Of Ediblesmentioning
confidence: 99%
“…One of the most significant factors in the decision to use cannabis-infused edibles is the perception that edibles avoid the harmful toxins and health risks that may be associated with smoking (Murphy et al, 2015). Because the health risks associated with smoking tobacco are substantial (reviewed in Center for Disease Control and Prevention, 2010), the risks of smoked cannabis are often assumed to be similarly severe.…”
Section: Promises Of Ediblesmentioning
confidence: 99%
“…Their health benefits and risks have been examined in recent reviews [7–12], and an emerging literature suggests consumption of high-THC cannabis flowers is associated with greater severity of dependence [13] and adverse psychological outcomes [5, 14]. The proliferation of new high-THC products (e.g., “shatter”) and methods of consumption (e.g., “dabbing”), particularly in jurisdictions allowing recreational and/or medical cannabis sales [15, 16], has raised additional questions, as their use and consequences have only recently begun to be examined [1721], and it is difficult to predict how legalization will influence their demand [22, 23]. Further, there is no consensus about whether individuals who use products with higher concentrations of THC titrate their doses [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…We extend the definition to include the different derivatives of cannabis (flowers, edibles, concentrates), as well as routes of administration (smoking, eating, vaporizing). The various cannabis “delivery systems” (derivatives and routes of administration) have their own set of reported benefits and drawbacks (Murphy et al, 2015). Some harm reduction techniques related to smoke inhalation include: using cannabis strains with a high THC 1 content, refraining from using cannabis with tobacco or other dried herbs, using cannabis that is free of contaminants and adulterants, omission of the Valsalva maneuver 2 and prolonged breath holding, and the use of alternative delivery systems such as pipes, vaporizers, and oral preparations (Grotenhermen, 2001).…”
Section: Introductionmentioning
confidence: 99%